Creative Risk‐Taking: Developing Strategies for First Year University Students in the Creative Industries. (25th September 2018) - Choi, Jaz Hee‐Jeong; Payne, Alice; Hart, Phoebe; Brown, Alice
Abstract: This article reports on the findings of a study investigating creative risktaking behaviours of the commencing university students enrolled in three units across three disciplines: Interactive and Visual Design, Fashion Design, and Film, Screen and Animation. The study employs an action research methodology in order to help students develop confidence and competence in creative risk‐taking. Upon analysis from relevant literature three key provisions for the study are proposed, being: P1 An open and playful learning environment that encourages sharing and challenging multiple perspectives; P2 An adequate period of time for students to develop and revise creative concepts; and P3 Opportunities to assess their own performance in developing creative risk‐taking capacities. The study draws on the students' written self‐reflections to identify the key challenges and opportunities in encouraging creative risk‐taking among first year students, which are challenges of collaboration; creative resilience and self‐efficacy; and balancing creativity with technical competency. The article suggests several ways that educators can encourage students to take creative risks within higher education in preparation for careers in the creative industries.